Efek Radial Shock Wave Therapy pada Latihan Gliding Nervus Medianus terhadap Derajat Nyeri dan Fungsional Tangan Penderita Carpal Tunnel Syndrome - Amalina, Nurika; Indriastuti, Lanny; Julianti, Hari Peni; Zuhdiana, Hindun; Kusumawati, Noviolita Dwi (RSUP Dr. Kariadi, 2021)
Background: Carpal tunnel syndrome (CTS), which was resulted from local compression of the median nerve, was a common entrapment neuropathy. Median nerve gliding exercise required a combination of other conservative therapies to provide optimal clinical improvement in CTS. Radial shock wave therapy (RSWT) was a safe, effective, practical, and non-invasive therapeutic method, can be used as a additional therapy for relieving pain and disability in CTS patients. Objective: This study was aimed to examine the effect of RSWT on median nerve gliding exercise on improving the degree of pain and hand functional scores in patients with CTS. Method: This study was a randomized controlled trial. The subjects were 22 patients from the Physical Medicine and Rehabilitation Polyclinic of RSUD KRMT Wongsonegoro, Semarang. They were divided into 2 groups randomly. The intervention group (n=11) was received RSWT 4 times in median nerve gliding exercise 3 times a day, every day for 4 weeks. The control group (n=11) was received only median nerve gliding exercise. The degrees of pain were measured with a manual algometer and hand functional scores were assessed by BCTQ. Results: The mean of improving pain degree were 2,53 + 0,74 kg/cm2 and 2,38 + 1,25 kg/cm2 in intervention and control group, respectively. An independent t-test showed that there were significant differences in improving pain degree between intervention and control group (p=0,016). The mean of improving BCTQ scores were -11,36 + 4,59 and -6,18 + 3,76 in intervention and control group, respectively. An independent t-test showed that there were significant differences in improving BCTQ scores between intervention and control group (p=0,009). Conclusion: RSWT was improved the degree of pain and increased the hand functional scores of CTS patients who received median nerve gliding exercises. Keywords: radial shock wave therapy, carpal tunnel syndrome, gliding exercise